Reduction in leaf growth and stomatal conductance of capsicum (Capsicum annuum) grown in flooded soil and its relation to abscisic acid - Ismail, Mohd Razi; W. J., Davies (Universiti Putra Malaysia Press, 1997)
The effects of soil flooding on leaf growth, water relations, stomatal responses and abscisic acid (ABA) content in young capsicum (Capsicum annuum L.) plants were studied under controlled environmental conditions. Soil flooding induced early stomatal closure and leaf growth reduction without any reduction in leaf water deficit. The undetectable changes in leaf water potential of plants grown in flooded soil persisted for 4 d. Thereafter, leaf water potential was reduced to the minimum values. Xylem sap abscisic acid concentration was increased after 24 h of soil flooding, and increased rapidly with duration of flooding. Plants grown in flooded soil had higher concentration of abscisic acid in leaves and flowers than the well watered plants. Under both conditions, abscisic acid concentrations was higher in flowers than in leaves.